PERANAN PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) PERPAJAKAN DAN PENYIDIK POLRI DALAM PENANGANAN TINDAK PIDANA PERPAJAKAN - Siti Maimana Sari Ketaren; Alvi Syahrin; Madiasa Ablisar; Muhammad Hamdan (USU LAW JOURNAL, 2013)
The tax is an important thing as welfare state as one of income source for the increasing of social welfare in a state. Indonesia is one of nation that put tax as one of state income source although it has not yet put tax as one of increasing of society welfare. In the law enforcement process include the tax law enforcement, it always face to criminal justice system. This system is one of system to eradicate the crime in a society. Crimnal justice system has any components, i.e. police, attorney, court, and correctional instituation. In addition to the component of the criminal justice system, there is one specific component for the case of tax, i.e. the civil servant investigator (PPNS) who has responsibility to do the investigation if there is a crime in tax to support the public attorney in handle the tax case. The role of PPNS as instuation out of Police aims to help the task of police in to the investigation that determined in the Crime Procesure Law and Act No. 2 of 2002 concerning to the Police of republic of Indonesia. PPNS or Police must helpot one to the others especially in provide the required information about the crime case to support the crime investigation actually and completely to avoid the intersect of authority in do the investigation that requires the coordination and supervision between the related instituation in enforcement, and socialization of the rule related to the authority in any investigation and to obtain the understanding about the task and authority for each instituation. Through this socialization it will eliminate the gap between the instituation and realize the complete instituation.